Effectiveness of Steriliztion Infrared Dry Heat Sterilization and Sterility Of Dentistry Tools - Sariyem Sariyem; Sadimin Sadimin; Prasko Prasko (Jurnal LINK, 2013)
Transmission of infection can be occured  from the use of instruments that are not sterile, to break the chain of transmission of the infection, it is necessary to carry out the sterilization of medical devices with the correct procedures such as sterilization by dry heat or infrared can also with other methods. The purpose of this study to know the number of microorganisms and decrease the effectiveness of both the sterilization sterilize dental instruments.The reacherd was conducted in the laboratory using the method of experimental research, design research is one group pretest-posttest. The data have been acquired and processed statistically tested by Paired T-Test and Independent Test.Based on the results, the data is a decline in the number of bacteria in the infrared sterilization, but still found breeding of bacteria in sterilized tools. Decline in the number of bacteria in dry heat sterilization and no breeding of bacteria in all the tools are sterilized. The results of statistical tests Paired T-Test were both obtained p value = 0.000, so it can be said that the infrared sterilization and dry heat sterilization is effective in reducing the number of bacteria on equipment in dentistry. The statistical result obtained Independent T-Test p value: 0.626, which means there are no significant differences between the infrared sterilization and dry heat sterilization in killing microorganisms.